?NITRATE AND NITRITE CONTENTS IN FOOD OF PLANT ORIGIN IN PAKISTAN ? (Biological Sciences - PJSIR, 1994)
Nitrate and nitrite contents of commonly consumed cereals, pulses and vegetables in four provinces of Pakistanindicated highest levels (6490 ppm) in vegetables. Cereals from the NWFP contained more nitrites than those collectedfrom other provinces. The lowest amounts of nitrate and nitrite were detected in the pulses.